2021
DOI: 10.1002/adom.202101602
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine Oxide Additives for High‐Brightness Inorganic Perovskite Light‐Emitting Diodes

Abstract: Regarding their application as light emitters in light-emitting devices, perovskites enable easy to obtain bandgap tunability (1.2 eV ⩽ E g ⩽ 3.5 eV) [10] and emission over a wide spectrum with generally low full width at half maximum (FWHM < 20 nm) allowing very color pure devices. [11]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…CsPbBr 3 films with various concentrations of DEABr (0, 9, 11, and 13 mg/mL) were fabricated by one-step spin-coating on EA-PEDOT:PSS, and crystal structural analysis was performed by X-ray diffraction (XRD), as illustrated in Figure a. The diffraction peaks at 15.2, 21.5, 30.7, 34.3, and 37.7° can be assigned to the (100), (110), (200), (201), and (211) planes of the orthorhombic ( Pnma ) CsPbBr 3 crystal, consistent with previous reports. , According to the information on the peak positions and intensity ratios of each diffraction peak in the comparison chart, it is found that all perovskite films show almost the same XRD patterns, indicating that the crystal structure and growth orientation of CsPbBr 3 are not significantly affected by the added DEABr. To further investigate the effect of DEABr on the surface morphology of the perovskite film, surface morphologies of DEABr-CsPbBr 3 films with different concentrations were compared by overhead scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…CsPbBr 3 films with various concentrations of DEABr (0, 9, 11, and 13 mg/mL) were fabricated by one-step spin-coating on EA-PEDOT:PSS, and crystal structural analysis was performed by X-ray diffraction (XRD), as illustrated in Figure a. The diffraction peaks at 15.2, 21.5, 30.7, 34.3, and 37.7° can be assigned to the (100), (110), (200), (201), and (211) planes of the orthorhombic ( Pnma ) CsPbBr 3 crystal, consistent with previous reports. , According to the information on the peak positions and intensity ratios of each diffraction peak in the comparison chart, it is found that all perovskite films show almost the same XRD patterns, indicating that the crystal structure and growth orientation of CsPbBr 3 are not significantly affected by the added DEABr. To further investigate the effect of DEABr on the surface morphology of the perovskite film, surface morphologies of DEABr-CsPbBr 3 films with different concentrations were compared by overhead scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…It also provided a creative strategy for dealing with other optoelectronic applications that demand a constant band gap. 37…”
Section: Introductionmentioning
confidence: 99%
“…This work provided a basis for preparing reliable and effective PeLEDs with pure red emission and was expected to promote the development of the future displays. It also provided a creative strategy for dealing with other optoelectronic applications that demand a constant band gap …”
Section: Introductionmentioning
confidence: 99%
“…Such types of Lewis bases have been reported to reduce the dangling bond density by establishing Pb-O bonds, which eliminates the ionic defects of Pb 2+ ions. [23][24][25] Among them, TOPO exhibits a strong coordination ability of the oxygen atom in the PvO group to Pb 2+ ions, thereby suppressing non-radiative recombination by a reduction in ionic defects acting as trap sites. Therefore, TOPO has been an appealing defect passivator for enhancing the device performance in photovoltaics and lightemitting diodes based on metal halide perovskites, regardless of the dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported the passivation of bulk defects using TOPO via addition into perovskite solutions or dripping a TOPO solution into a perovskite antisolvent during spin coating. 24,25 Those additive approches were almost ineffective with respect to perovskite crystallinity and photovoltaic performance. The failure of TOPO in forming better crystalline perovskites despite its coordination with Pb 2+ ions remains unresolved.…”
Section: Introductionmentioning
confidence: 99%